Revised upper Paleozoic stratigraphy of the Blacks Harbour-Beaver Harbour area, New Brunswick, Canada: Evidence from new bedrock mapping and palynology - Hinds, Steven J.; Park, Adrian F.; Johnson, Susan C.; McLean, Duncan (Atlantic Geoscience, 2024)
Upper Paleozoic sedimentary rocks form outliers delineated by large strike-slip faults in the Blacks Harbour-Beaver Harbour area in southwestern New Brunswick. Currently included in the Upper Devonian Perry Formation, and Visean–Pennsylvanian Mabou Group (Balls Lake Formation) and Cumberland Group (Lancaster Formation), these units have been subject to varied interpretations since the initial mapping during the 19th century. The Perry Formation, a red bed sequence consisting of coarse conglomerate, sandstone, minor shale, and mafic volcanic rocks, has yielded plant fossils (indeterminate debris and decorticated stem and root fossils) considered to be broadly Devonian, and most likely Famennian. The ‘Carboniferous’ strata have proven more intractable. Three units have been defined by mapping: Lighthouse Cove Formation (previously: ‘Fish Plant Beds’), Cripps Steam Formation, and Russels Point Formation (previously: ‘Beaver Harbour Formation’). These units have yielded plant fossils in the form of indeterminate debris and decorticated stem and root fragments that various workers have attributed to the Silurian, Devonian, Mississippian, or Pennsylvanian. New palynological analyses from the Perry Formation (at Tunaville) and Russels Point Formation (at Woodland Cove and Russels Point) have yielded stratigraphically significant assemblages. The Tunaville assemblage, the first miospores from anywhere in the Perry Formation, and roughly in the middle of the local sequence, is lower to middle Famennian. Two miospore assemblages are from near the base of the Russels Point Formation: one shows a possible range from Tournaisian to Holkerian (middle Visean), and the second is better constrained between Chadian and Holkerian (lower to middle Visean). Only the Lighthouse Cove Formation (‘Fish Plant Beds’) failed to yield any miospore assemblages; however, mapping and structural considerations are compatible with this unit being older than the Russels Point Formation and younger than the Perry Formation and most likely Tournaisian to lower Visean. One new stratigraphic relationship has been located along the southern shore of Deadmans Harbour where an angular unconformity occurs between red beds of the Perry Formation and grey beds of the overlying Russels Point Formation. Contrasting deformation styles in these units related to displacement on the Belleisle Fault constrain a major phase of strike-slip movement to the Famennian–Tournaisian interval.